2017
DOI: 10.18632/oncotarget.18554
|View full text |Cite
|
Sign up to set email alerts
|

Phase I dose-escalation study of the c-Met tyrosine kinase inhibitor SAR125844 in Asian patients with advanced solid tumors, including patients with MET-amplified gastric cancer

Abstract: SAR125844 is a potent and selective inhibitor of the c-Met kinase receptor. This was an open-label, phase I, multicenter, dose-escalation, and dose-expansion trial of SAR125844 in Asian patients with solid tumors, a subgroup of whom had gastric cancer and MET amplification (NCT01657214). SAR125844 was administered by intravenous infusion (260–570 mg/m2) on days 1, 8, 15, and 22 of each 28-day cycle. Objectives were to determine the maximum tolerated dose (MTD) and to evaluate SAR125844 safety and pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…In gastrointestinal tumors, several clinical studies have addressed the predictive role of MET dysregulation as an actionable target. These investigations have tested HGF/MET pathway inhibitors as single agents or in combination with other therapies, and have reported different outcomes [20,47,155]. For instance, when 71 patients with advanced hepatocellular carcinoma were enrolled in a placebo-controlled double-blind phase II study, the results showed that tivantinib was associated with a trend towards improved time to progression (2.7 vs. 1.7 months, p ¼ .03), PFS (2.2 vs. 1.4 months, p ¼ .02), and OS (7.2 vs. 3.8 months, p ¼ .01) in the MET-high patients [44].…”
Section: Iii-met Aberrant Activation In Tumor Tissue As a Predictive mentioning
confidence: 99%
“…In gastrointestinal tumors, several clinical studies have addressed the predictive role of MET dysregulation as an actionable target. These investigations have tested HGF/MET pathway inhibitors as single agents or in combination with other therapies, and have reported different outcomes [20,47,155]. For instance, when 71 patients with advanced hepatocellular carcinoma were enrolled in a placebo-controlled double-blind phase II study, the results showed that tivantinib was associated with a trend towards improved time to progression (2.7 vs. 1.7 months, p ¼ .03), PFS (2.2 vs. 1.4 months, p ¼ .02), and OS (7.2 vs. 3.8 months, p ¼ .01) in the MET-high patients [44].…”
Section: Iii-met Aberrant Activation In Tumor Tissue As a Predictive mentioning
confidence: 99%
“…Additionally, there were no significant changes of the heart rate in mice receiving LAP compared with the sham group ( Figure 1B). malignancies are thought to be caused by an aberrant tyrosine kinase function [1][2][3]. However, some TKIs have been reported to cause a significant prolongation of the electrocardiographic QTc interval when used to treat patients with advanced carcinoma [4].…”
Section: Lap Caused Qtc Prolongation In the Mouse Modelmentioning
confidence: 99%
“…Lapatinib (LAP) and sorafenib (SOR) represent a unique group of multitargeted, active small-molecule tyrosine kinase inhibitors (TKIs) currently used to treat hematological/oncological malignancies. Planning for dose escalation has been considered for their clinical use, as many malignancies are thought to be caused by an aberrant tyrosine kinase function [1][2][3]. However, some TKIs have been reported to cause a significant prolongation of the electrocardiographic QTc interval when used to treat patients with advanced carcinoma [4].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetics studies were performed and analyzed in several species from mice to dog [ 43 ]. Phase I dose escalation and dose expansion study in patients with advanced tumors showed modest antitumor response in patients with MET amplified gastric cancers at 570 mg/m 2 and was well tolerated [ 44 ]. A first in human phase 1 clinical trial was performed in patients with NSCLC ( Table 1 ).…”
Section: Tyrosine Kinase Inhibitors With Selectivity For C-metmentioning
confidence: 99%